Greenhouse effect and the law in Malaysia: obligation and compliance towards international standards / Adibah Anwar, Nur Malisa Ahmad Tulus, Mohd Sholihin Shamsuddin - Anwar, Adibah; Ahmad Tulus, Nur Malisa; Shamsuddin, Mohd Sholihin (2008)
This research is about greenhouse effect and the law in Malaysia by looking at the obligation and compliance of Malaysia towards international standards. There are two main effects of greenhouse gases which is climate change and global warming. Our research focusing on climate change and we limit our focus in Shah Alam despite of Malaysia due to limited time of research. Hence, the objective of this research is to study Malaysia's obligation under international convention on climate change. Malaysia has been a party to United Nations Framework Convention on Climate Change (UNFCCC) and had ratified Kyoto Protocol. Therefore, Malaysia needs to fulfill the obligation made by UNFCCC. By doing this research, we had found that Malaysia had fulfilled the obligation by sending a National Communication once required by UNFCCC. This research also looks at the Malaysia's compliance towards international obligation. As require under National Communication, Malaysia had done and still doing certain inventories, mitigation and adaptation. Malaysia also has many acts which can be used to reduce gas emission and effects of climate change such as Environment Quality Act, National Forestry Act and etc. In doing this research, we had found that lack of enforcement of law is a problem facing by Malaysia in order to reduce greenhouse effects.